Culture in translation : the anthropological legacy of R.H. Mathews - Mathews, R. H. (Robert Hamilton), 1841-1918 (Aboriginal history monograph series, 2007)
"Almost 90 years on from his death, this is the first book-length collection of the writings of Robert Hamilton Mathews. It has been a long wait for the Australian-born surveyor who began his career as an anthropologist at the age of 52 with the 1893 publication of a brief paper on New South Wales rock art. Apart from a few short booklets, Mathews book of 1905, Ethnological Notes on the Aboriginal Tribes of New South Wales and Victoria, was his only work of anthropology to be published as a freestanding volume. A reprint of a long article published the previous year, it was a modest tome in that age of doorstopper monographs - 'little more than a pamphlet' according to Mathews' friend, the British folklorist E.S. Hartland. There was certainly an expectation that a writer so prolific as Mathews would disseminate his work in a substantial book. As Arnold van Gennep, the Parisian anthropologist, pointed out to him, 'your publications are for the most part overlooked because they are scattered amongst a mass of periodicals and it is a very difficult matter to have them all at one time in hand ... '. Van Gennep recommended that Mathews immediately arrange for their 'publication in 2 or 3 volumes' - advice endorsed by Hartland who was enlisted to work with Mathews ornithologist son Gregory, then living in England, to place a manuscript with a London publisher (see Correspondence, this volume). But these efforts were unsuccessful and R.H. Mathews died in 1918 without ever publishing his magnum opus."--Provided by publisher